2006
DOI: 10.3844/ajassp.2006.2134.2135
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Curve of a Fuel Cell

Abstract: Abstract:The aim of this study was to deliver information about the features of fuel cells. It cover analysis of theory and experiment done using a set of tool called Hydro Genius Teach. The experiment is about investigating the characteristic curve of a fuel cell from the processes of renewable energy. Others objectives of this study were to analyze current usage of renewable energy in the world and to do analysis on features of fuel cell as one of ways in renewable energy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…By representing the voltage drop across the external load expressed as a function of the current through that load, the socalled polarization curve may be obtained, which has traditionally characterized the performance of a fuel cell; this curve is actually helpful in explaining the chemistry and physics associated with fuel cell operation [26,27]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…By representing the voltage drop across the external load expressed as a function of the current through that load, the socalled polarization curve may be obtained, which has traditionally characterized the performance of a fuel cell; this curve is actually helpful in explaining the chemistry and physics associated with fuel cell operation [26,27]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The present research can be considered as belonging to the research field reported in the literature concerning the development of fuel cells [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ] and biofuel cells [ 28 , 54 , 55 , 56 , 57 ] for several purposes. This study positively extended applications to several pharmaceutical products (dyes) by a simple DMFC catalytic device (already performed on several alcoholic beverage samples [ 25 , 26 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Researches of different types have been performed in the past by some authors with the aim of using different fuel-cell-based devices for analytical [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ] (and energetic [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]) purposes. These researches have effectively shown the possibility of this kind of application, but only by means of particular and complex types of fuel cell, not useful for common application to real samples.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, several researches have been performed by some authors, with the aim of using different fuel-cell devices for energetic [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] and analytical [18][19][20][21][22][23][24] purposes. These researches have effectively shown the possibility to perform some analytical applications but only by means of particular Sensors 2020, 20, 3615 2 of 12 and complex types of fuel cells not useful for common application to real samples.…”
Section: Introductionmentioning
confidence: 99%